Risk factors for diabetes are higher among non‐heterosexual US high‐school students. Issue 7 (8th August 2018) - Beach, Lauren B; Turner, Blair; Felt, Dylan; Marro, Rachel; Phillips, Gregory L
Abstract : Low physical activity (PA), high sedentary behavior (SB), and overweight and obesity have been shown to associate with increased Type 2 diabetes risk among adolescents. We investigated PA, SB, and overweight and obesity among Youth Risk Behavior Survey (YRBS) respondents to determine if non‐heterosexual youth may be at increased diabetes risk compared to heterosexual youth. Weighted city and state YRBS data were pooled across 44 jurisdictions biennially from 2009 to 2015, resulting in a sample size of 350 673 students. Overall, 88.4% identified as heterosexual, 2.1% as gay or lesbian, 5.7% as bisexual, and 3.7% as unsure. With the exception of lesbian female students, after adjusting for age, race/ethnicity, body mass index, and survey year, all non‐heterosexual youth reported significantly fewer days per week of PA compared to their sex‐matched heterosexual counterparts. Similarly, compared to heterosexual female youth, bisexual and not sure female youth reported significantly more hours per day of SB. These PA and SB findings remained significant after adjustment for depressive symptoms and in‐school bullying among bisexual female youth only. In fully adjusted models, lesbian students were 1.85 times more likely to be overweight and lesbian, bisexual, and not sure female youth were 1.55 to 2.07 times more likely to be obese than heterosexual female students. No significant differences in SB, overweight, or obesity were found among gay, bisexual, or unsure male youth compared to heterosexual male youth. Non‐heterosexual youth may be at increased risk for developing type 2 diabetes mellitus compared to heterosexual youth. Future studies should characterize diabetes prevalence among non‐heterosexual youth.